Accuracy and Sensitivity of Coefficient Alpha and Its Alternatives with Unidimensional and Contaminated Scales. Issue 1 (2nd January 2023) - Xiao, Leifeng; Hau, Kit-Tai
ABSTRACT: We compared coefficient alpha with five alternatives (omega total, omega RT, omega h, GLB, and coefficient H) in two simulation studies. Results showed for unidimensional scales, (a) all indices except omega h performed similarly well for most conditions; (b) alpha is still good; (c) GLB and coefficient H overestimated reliability with small samples and short scales, and (d) sensitivity to scale quality reduced with longer scales. For contaminated scales, (a) all indices except omega h were reasonably unbiased with non-severe contamination; (b) alpha, omega total, and GLB were more sensitive in picking up contamination with shorter scales, whereas omega RT and omega h were not; and (c) coefficient H could not pick up contaminated items among high-quality items. For applied researchers, (a) supplementary information of scale characteristics helps choose the appropriate index; (b) comparing different scales with one golden standard is inappropriate; (c) omega h should not be used alone.